New observations on Mallomonas getseniae comb. et stat. nov. (Chrysophyceae, Synurales) - Bessudova, Anna; Likhoshway, Yelena V. (Phytotaxa, 2023)
Applying of electron microscopy upgrades our knowledge on single-celled flagellates covered with siliceous scales and bristles their morphology and biodiversity. We propose a new combination and taxonomic status of Mallomonas getseniae (Voloshko) Bessudova comb. et stat. nov. based on an earlier description of scale and bristle morphology of a variety of Mallomonas striata var. getseniae Voloshko and our new data, which complement it. The species belongs to the section Striatae and have large scales, labyrinth-like reticulation on the dome and the posterior flanges with irregularly spaced large pores. The combination of those distinctive features of scale morphology is unique and allows raising the variety of M. striata var. getseniae to the species as M. getseniae. The supplement of the description of M. getseniae is based on a wide set of scales and bristles from Lake Baikal, which significantly enlarges their size variation The paper gives a first image of bristles of the species. Dynamics of occurrences of siliceous components of the species in Lake Baikal says that it develops under the ice (in March).